Meclis-i Meşâyih defterleri (İstanbul)
9 cilt (1. c. 796 sayfa ; 2. c. 722 sayfa ; 3. c. 716 sayfa ; 4. c. 637 sayfa ; 5. c. 666 sayfa ; 6. c. 626 sayfa ; 7. c. 650 sayfa ; 8. c. 625 sayfa ; 9. c. 748 sayfa)